Plastic buckling of simply supported compressed plates - Pride, Richard A.; Heimerl, George J. (National Advisory Committee for Aeronautics, 1949)
Tests were made of 14S-T6 aluminum-alloy square tubes to determine the critical compressive stress of simply supported flat plates in the plastic range. Excellent agreement is shown with with Stowell's theory for plastic buckling which is based upon a deformation theory of plasticity, close agreement with two other deformation-type theories of plastic buckling and withthe secant-modulus method, and marked disagreement with a buckling theory based upon a flow theory of plasticity.
Date of issue: April 1949.
Report no. NACA-TN-1817.
Keywords: Aluminum alloys.; Tubes.; Deformations (Mechanics); Buckling (Mechanics); Plasticity.; Pipe.; elektronické knihy; electronic books